Resource allocation and supplier relationship management towards the performance of the manufacturing industry: Evidence from the paint manufacturing firms in Harare, Zimbabwe - Emmanuel T. Denhere; Lovemore Chikazhe; James Kanyepe (Cogent Business & Management, 2023)
Resource and supplier relationship management continues to play a critical role in the efficiency of the supply chain and its competitive positioning. The current study sought to establish how the paint manufacturing industry's performance is influenced by resource allocation (finance, human, physical, and information resources) and supplier relationship management (systematic collaboration, activities programs, and review meetings) and their ultimate contribution to organizational performance. The objectives of this study were to establish the effect of resource allocation on supplier relationship management and determine how supplier relationship management influences the performance of the paint manufacturing industry. Using a simple random sampling method, data were collected from 116 employees involved in the procurement process from 30 paint manufacturing firms in Harare. A questionnaire with Likert-type questions was distributed electronically to collect the data. This study established that there is a high inadequacy of resources to support the supplier relationship management system. A greater percentage of organizations (77.5%) employ procurement staff with the necessary qualifications and experience to manage the buyer-supplier relationship. The study further revealed that some organizations (98%) within the paint manufacturing industry do not have websites for supplier interaction due to limited financial resources, thereby impacting their supplier information resources. This study contributes to the existing body of knowledge by providing new insights into the need for sufficient resource-supplier relationship management, as it greatly contributes to the performance of the paint manufacturing sector.
Keywords: 650; organisational performance; resource allocation; supplier relationship management; Zimbabwe